(untitled) (Medical Forum Monthly, 2024)
Objectives: To see the association of serum electrolyte derangement with severity of dehydration. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the Department of Peadiatric Medicine, Nishtar Medical College and Hospital, Multan from March 2016 to August 2016. Materials and Methods: Consecutive 107 children with acute diarrhea having dehydration were included in this cross-sectional study. Serum sodium and potassium levels were analyzed to see their association with severity of dehydration by applying ANOVA test using SPSS – 20. Results; Out of these 107 children having acute diarrhea, 59 (55.1%) were boys and 48 (44.9%) were girls and their mean age was noted to be 19.12 ± 8.89 months (range; 7 months to 36 months). Mean age of the boys was 15.29 ± 7.25 months while that of girls was 23.83 ± 8.49 months (p=0.000) and 58 (54.2%) were aged more than 1 year. Sixty five (60.7%) were from urban areas, 82 (76.6%) had poor background, 65 (60.7%) had history of stools less than 6 during last 24 hours. Mean duration of diarrhea was 5.13 ± 2.23 days and 74 (69.2%) presented with duration of less than one week of onset of the diarrhea. Fever was present in 65 (60.7%) and associated vomiting was present in 91 (85%) our study cases. Mean serum sodium level in our study was 133.65 ± 3.18 nmol/L while mean serum potassium level was 3.82 ± 0.625 nmol/L Conclusions: High frequencies of serum electrolyte derangement was noted in our study and this serum electrolyte derangement (hyponatremia and hypokalemia) was significantly associated with severity of the dehydration. Severity of dehydration is a predictor of hyponatremia and hypokalemia which ultimately lead to disease morbidity and mortality, hence these patients need to be monitored appropriately for better clinical outcomes.